Lipids, biomembranes and membrane proteins - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Properties of biomembranes, Types of lipid bilayer phases, Types of fatty acyl chains, Phospholipases, Types of membrane association, Membrane fusion
Reviewed at 2022/11/27